Determination of Lubricant Layer Thickness with an Allowance for Oil Absorption Capacity of Contacting Surfaces - Terentyev Dmitry (EDP Sciences, 2021)
The paper describes an analytical model for calculating an extreme pressure lubricant layer thickness with an allowance for oil absorption capacity of contacting surfaces. The model is practically assessed in laboratory conditions. The experimenting work shows that the speed of the relative displacement of contacting surfaces and the oil absorption capacity of their rough layers contributes to the thickening of the lubricant. The analysis of the results shows that it is the oil absorption capacity of rough layers that has the strongest influence on the change in the thickness of the extreme pressure lubricant layer.